Open access and the library (2019)
Libraries are places of learning and knowledge creation. While this mission has been the same for centuries, the way it is delivered is constantly evolving. Over the last two decades, digital technology—and the changes that came with it—have accelerated this transformation to a point where evolution starts to become a revolution.